Inserting Collaboration Values into a Digital Bilingual Storybook for Teaching English in Grade 5 - Putu Sandra Yuliantari; Luh Putu Artini; IGA Lokita Purnamika Utami (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research is motivated by persistent limitations in the integration of collaborative values within English learning in elementary schools, where instructional practices remain largely teacher-centered and the use of interactive learning media is still minimal. Such conditions hinder students' opportunities to develop essential social and character values, particularly collaboration, alongside their language competence. In response to this gap, the present study aims to analyze the integration and development of collaboration values—specifically caring, sharing, and cooperation—within bilingual digital storybooks designed for elementary-level English instruction. This research employs a Design and Development (D&D) approach, combining document analysis techniques with expert evaluation to ensure both content validity and pedagogical relevance. Data were analyzed using a combination of descriptive qualitative and quantitative approaches, allowing for a comprehensive understanding of how collaborative values are embedded within the narrative and instructional structure of the storybooks. The findings reveal that the value of collaboration has been systematically integrated through two complementary strategies: implicitly, through storytelling narratives that model cooperative behavior among characters, and explicitly, through interactive tasks that require students to practice sharing, caring, and cooperating directly. Furthermore, the integration of these values is developed progressively, moving from a developing level toward a more advanced level as students engage further with the storybook content. These results indicate that bilingual digital storybooks serve as an effective medium not only for enhancing English language proficiency but also for strengthening students' collaborative character. This study contributes theoretical and practical insights for educators and developers seeking to design interactive, character-based digital learning materials for young learners.